Dynamic near-infrared spectroscopy assessment as an important tool to explore pulmonary arterial hypertension pathophysiology. Issue 1 (5th January 2017) - Dimopoulos, Stavros; Tzanis, Giorgos; Karabinis, Andreas; Nanas, Serafim
With great interest we read the recent article by Panagiotou et al . [1] in which the authors investigated the correlation between tissue oxygen measurements ( S tO2 ) at rest and during constant-workload exercise with the analogous measurements of mixed venous oxygen saturation at the level of pulmonary artery ( S vO2 ) and inferior vena cava in patients with pulmonary arterial hypertension (PAH). In this study, the authors used near-infrared spectroscopy (NIRS) to assess the vastus lateralis muscle tissue oxygenation during exercise. Near-infrared spectroscopy: a useful methodology for pulmonary arterial hypertension http://ow.ly/7wwQ3065Cpb